A theorem of differential mappings of Riemann surfaces - Peichu Hu; Mingze Yang (International Journal of Mathematics and Mathematical Sciences)
In this paper, we have extended S.S. Chern's second basic theorem about holomorphic mapping between two Riemann surfaces to more general case, and also obtained two similar results.